EDUCAÇÃO PARA A MAIORIDADE DIANTE DO RACISMO EM CONTEXTOS DIVERSOS: LIVROS DIDÁTICOS DE HISTÓRIA DO ENSINO FUNDAMENTAL I - FERNANDA CALAZANS CARVALHO (2024)
The present study presents some reflections from an ongoing research. For now, based on the concepts of "race," racism, and ethnicity, our aim is to reflect on the education of children in the early years of elementary school. The research is characterized as qualitative and documentary, involving the analysis of bibliographic materials, namely, history textbooks for the first cycle of elementary education. Drawing on authors such as Munanga, Fanon, Stuart Hall, and Mwewa, among others, we engage with Kantian concepts of "minority" and "majority," which, to some extent, underpin Adorno's concept of "emancipation" that we will be working with. This investigation is justified insofar as if "races" do not exist biologically, genetically, or scientifically, then the racist individual acts and thinks under the guardianship of others – minority – which presupposes the existence of different "races" and their hierarchical ordering. We conclude that it is necessary to undertake an educational formative process aimed at subjective emancipation or achieving majority. Since racism persists, it can be said that there is still no collective majority regarding the dismantling of racial hierarchies.